Perancangan dan Pengembangan Sistem Konseling Siswa di SMK Satu Bangsa Harmoni - Hannuella, Albert Ricardo; Christian, Yefta (Telcomatics, 2024)
Satu Bangsa Harmoni Vocational School is a Batam private school that provides vocational education in Batam City which has been operating since 2008. Satu Bangsa Harmoni Vocational School still uses conventional methods in managing case and counseling data. This research is intended to develop a web-based student counseling system to make it easier for schools to manage student, case and counseling data effectively. The system was designed using the PHP programming language, Codeigniter 4 Framework, MySQL database, and Agile Scrum as a framework. With the counseling management system that has been implemented, it is hoped that it will make it easier for Satu Bangsa Harmoni Vocational School to manage data